Kemitraan Masyarakat - Akademik: Mengembangkan Bahan Ajar Berbasis Kearifan Lokal pada Guru Sekolah Dasar - Akhmad Kadir; Fredrik Sokoy; Aisyah Ali (LPPM Uncen, 2026)
Local wisdom is an essential part of the life of indigenous communities, not only strengthening cultural identity but also holding the potential to enrich the learning process in schools. Through this community service activity, a local culture-based teaching supplement was developed to support elementary school teachers in linking lessons to values that are alive in the community. The activity took place at SD YPK Ifar Babrongko, Kampung Yoboi, and involved direct collaboration between academics and the local indigenous community. The implementation was carried out through field observation, interviews with community leaders and teachers, group discussions, and pilot testing of teaching materials in a learning environment integrated with nature and local culture. The results show that teachers began to realize the importance of local culture as a learning resource. They were not only able to develop culture-based teaching materials but also demonstrated a shift in teaching methods that were more contextual and closer to the students' lives. As a contribution to community service, this activity successfully created a collaborative space for co-producing culturally responsive educational knowledge between the academic community and indigenous communities. The development of this learning supplement not only strengthened the pedagogical capacity of teachers in indigenous areas but also fostered institutional partnerships between universities and local communities in supporting cultural preservation and improving the quality of primary education.